Perancangan Artbook Storytelling Astrologi Tiongkok untuk Anak-Anak - Meindanu Dimas Prasetyo; Aditya Nirwana; Didit Prasetyo Nugroho (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
At present, specifically millennial generation, both children and teenagers in Indonesia are more familiar with the popularity of western-style astrology than Chinese astrology. Chinese astrology is assumed with ancient and boring things. That is because the way how to present eastern astrological merely informative content, such as history books, eastern astrological knowledge, etc. without containing of visual storytelling content. For this reason, there is an alternative media solution to solve these problems, named